Delaney and the Motor Vehicle Insurance Directives: lessons for the teaching of EU law. Issue 4 (2nd October 2017) - Marson, James; Ferris, Katy
ABSTRACT: A recent series of cases relating to the EU Motor Vehicle Insurance Directives and their application in the UK makes for interesting reading. It is the UK's negligent transposition, and a lack of knowledge and awareness by lawyers and judges in the cases of the interaction between domestic and EU law, which compounds the negative effects. The issues raised in Delaney v Pickett [2011] and Delaney v Secretary of State [2014] do not just generate concern as to the implications they have for the application of EU law principles, but have resonance with the way in which EU law is taught in many universities. In this article we suggest that reconsidering the method and purpose of EU teaching may better serve the EU-lawyers needed for the future.